Changes in Yield and Quality of Agar from the Agarophytes, Gracilaria fisheri and G. tenuistipitata var. liui Cultivated in Earthen Ponds - Anong Chirapart; Jittima Munkit; Khanjanapaj Lewmanomont (Agriculture and Natural Resources, 2006)
Gracilaria fisheri and G. tenuistipitata var. liui cultured in earthen ponds containing shrimp farm effluent (P1) and ambient seawater (P2), were collected from October 1998 to March 1999 for agar extraction. Yield and quality of agar extracted from both Gracilaria species were determined. Agar yields with highest value were obtained from G. fisheri grown in P2 (43.48±1.00%) and P1 (40.07±2.06%) while G. tenuistipitata var. liui yielded only 35.75±0.42% and 39.28±0.50% agar in P2 and P1, respectively. Yields of agar from each species were not significantly different when grown in P1 and P2 (p>0.01). Gel strength of agar from G. fisheri showed a maximum value of 623 g/cm2 in P1 and 658.6 g/cm2 in P2 while G. tenuistipitata var. liui gave a maximum value of 565.8 g/cm2 in P1 and 611 g/cm2 in P2 during low seawater temperature of 28.5°C in December 1998. Agar gel strength from G. fisheri was inversely related to total dissolved inorganic nitrogen (r = -0.54 in P1; r = -0.77 in P2, p<0.01, n = 12) while G. tenuistipitata var. liui showed a positive correlation (r = 0.41 in P1; r = 0.88 in P2, p<0.01, n = 12). Increasing in agar gel strength of G. tenuistipitata var. liui was observed during decreasing in alkalinity in seawater. Agars extracted from both G. fisheri and G. tenuistipitata var. liui gave rather high gelling temperature during dry season. The agar quality of both cultivars showed relation with nutrient and environmental factors of the seawater.